(untitled) - Reynolds, John (New York, NY, 2002)
Courtyards is an artful, informative exploration of courtyards, from their origins in early civilization to contemporary design concepts. Architects and landscape architects will repeatedly turn to the detailed guidelines for reference, gain a greater sense of balance between building and garden, and cultivate optimal green space by using the practical planting tips. Over one hundred photographs and drawings illustrate the concepts written about by an authority and passionate scholar in his field
Keywords: Courtyard houses,Courtyard gardens,Architecture and climate,Nhà sân vườn